TINJAUAN LITERATUR SISTEMATIS TENTANG LITERASI EKONOMI DIGITAL SEBAGAI KOMPETENSI ABAD 21 DALAM PENDIDIKAN EKONOMI - Muhammad Roestam Afandi Afandi; Sukirno (Jurnal Sosialita, 2025)
This study aims to analyze and map digital economic literacy in the context of 21st-century economics education using a Systematic Literature Review (SLR) approach. Digital economic literacy is viewed as one of the essential competencies of the 21st century, linking an understanding of economic concepts with skills in using digital technology. This competency emphasizes not only an understanding of economic theory but also the skills to access, process, and utilize digital information for more rational economic decision-making. The research method used SLR using the PRISMA protocol. The articles analyzed were obtained from national and international databases with publications spanning through 2025. Article selection was conducted through four stages: identification, screening, eligibility, and in-depth analysis. The researchers' exploration of digital economic literacy in economics education generally highlights three main focuses. First, the integration of digital technology into the economics learning process to increase the interactivity and relevance of the material. Second, strengthening financial literacy and digital literacy competencies in an integrated manner so that students can adapt to global economic changes. Third, innovative pedagogical strategies that encourage critical thinking, problem-solving, creativity, and collaboration are discussed. The results of the study are expected to uncover challenges such as gaps in technology access, the readiness of educators, and the need for a curriculum that adapts to digital developments. This research provides theoretical contributions to the development of the concept of digital economic literacy, as well as practical implications in designing economic learning strategies that are relevant to the needs of the 21st century.